Local Community Empowerment in the Special Autonomy Law in Papua Province - Usman Pakasi (Jurnal Studi Pemerintahan, 2012)
The establishment of the 2001 Special Autonomy Law in Papua Province is not exempted from economic, political and socio-cultural problems. The law is intended to empower the people by preserving their interests and upholding the basic rights of native Papuans. This research aims at finding out a theoretical understanding on the forms of local community empowerment during the implementation of special autonomy in Papua Province. The study is performed through a qualitative approach with a phenomenological strategy. The research was conducted at a location in Jayapura. Empirical data were obtained using the techniques of observation, in-depth interviews, and other secondary data. The implementation of Special Autonomy in Papua Province has brought forth a fundamental change in the approaches and policies of community development, particularly local community empowerment that includes indigenous communities, women, and religion. Local community empowerment in the economic and socio-cultural aspects represents the effort to improve the welfare and sense of justice within the local community in development.